2019
DOI: 10.1002/slct.201901064
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Nanoformulated Chemotherapeutic Drug Delivery (2015‐2019)

Abstract: An attempt was made to summarize the chemotherapeutic drug formulations at nanoscale. The number of biocompatible materials like carbohydrates, proteins, peptides, chitosan, and other water soluble materials would enhance the hydrophilicity of chemotherapeutic drugs. Some of the formulations were responsible for the improved anticancer activity, drug loading capability, higher encapsulation efficiency etc. Nanodrug formulations were engineered in such a way that hydrophobic anticancer agents were transformed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“… 211 It is observed that enhanced potency of 1,3 β-Glucan as an outer shell to chitosan nanoparticles loaded with paclitaxel can prevent hemolysis enabling effective therapeutic advantage against glioblastoma, thus overcoming the systemic toxicities due to paclitaxel alone with increased bioavailability. 212 The safety profile of drugs in nano formulations provides additional advantage compared to free drugs, 213 and further the cancer therapeutic is always at risk and disadvantage due to radiation toxicity, drugs like baicalein in its oral nanoform in preclinical evaluation have modulated the radiation response. 214 Cytarabine loaded liposomes in phase I/II clinical trials have shown additional safety as compared to free drug 215 in patients with secondary glioblastoma.…”
Section: Therapeutic Nps In Management Of Glioma/gbmmentioning
confidence: 99%
“… 211 It is observed that enhanced potency of 1,3 β-Glucan as an outer shell to chitosan nanoparticles loaded with paclitaxel can prevent hemolysis enabling effective therapeutic advantage against glioblastoma, thus overcoming the systemic toxicities due to paclitaxel alone with increased bioavailability. 212 The safety profile of drugs in nano formulations provides additional advantage compared to free drugs, 213 and further the cancer therapeutic is always at risk and disadvantage due to radiation toxicity, drugs like baicalein in its oral nanoform in preclinical evaluation have modulated the radiation response. 214 Cytarabine loaded liposomes in phase I/II clinical trials have shown additional safety as compared to free drug 215 in patients with secondary glioblastoma.…”
Section: Therapeutic Nps In Management Of Glioma/gbmmentioning
confidence: 99%